Asymmetric Multimetallic Mesoporous Nanospheres - Lv, Hao; Xu, Dongdong; Sun, Lizhi; Henzie, Joel; Lopes, Aaron; Gu, Qingyu; Yamauchi, Yusuke; Liu, Ben (Nano letters, 2019)
Mesoporous colloidal nanospheres with tailorable asymmetric nanostructures and multimetallic elemental compositions are building blocks in next-generation heterogeneous catalysts. Introducing structural asymmetry into metallic mesoporous frameworks has never been demonstrated, but it would be beneficial because the asymmetry enables the spatial control of catalytic interfaces, facilitates the electron/mass transfer and assists in the removal of poisonous intermediates. Herein, we describe a simple bottom-up strategy to generate uniform sub-100 nm multimetallic asymmetric bowl-shaped mesoporous nanospheres (BMSs). This method uses a surfactant-directed “dual”-template to control the kinetics of metal reduction on the surface of a vesicle, forming mesoporous metal islands on its surface whose spherical cone angle can be precisely controlled. The asymmetric BMS mesostructures with different spherical cone angles (structural asymmetries) and elemental compositions are demonstrated. The high surface area and asymmetric nature of the metal surfaces are shown to enhance catalytic performance in the alcohol oxidation reactions. The findings described here offer novel and interesting opportunities for rational design and synthesis of hierarchically asymmetric nanostructures with desired functions for a wide range of applications.